End-of-treatment PET/CT predicts PFS and OS in DLBCL after first-line treatment: results from GOYA - Kostakoglu, Lale; Martelli, Maurizio; Sehn, Laurie H; Belada, David; Carella, Angelo-Michele; Chua, Neil; Gonzalez-Barca, Eva; Hong, Xiaonan; Pinto, Antonio; Shi, Yuankai; Tatsumi, Yoichi; Knapp, Andrea; et al. (Blood advances, 2021)
GOYA was a randomized phase 3 study comparing obinutuzumab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) vs standard-of-care rituximab plus CHOP in patients with previously untreated diffuse large B-cell lymphoma (DLBCL). This retrospective analysis of GOYA aimed to assess the association between progression-free survival (PFS) and overall survival (OS) with positron emission tomography (PET)-based complete response (CR) status. Overall, 1418 patients were randomly assigned to receive 8 21-day cycles of obinutuzumab (n = 706) or rituximab (n = 712) plus 6 or 8 cycles of CHOP. Patients received a mandatory fluoro-2-deoxy-d-glucose-PET/computed tomography scan at baseline and end of treatment. After a median follow-up of 29 months, the numbers of independent review committee-assessed PFS and OS events in the entire cohort were 416 (29.3%) and 252 (17.8%), respectively. End-of-treatment PET CR was highly prognostic for PFS and OS according to Lugano 2014 criteria (PFS: hazard ratio [HR], 0.26; 95% confidence interval [CI], 0.19-0.38; P < .0001; OS: HR, 0.12; 95% CI, 0.08-0.17; P < .0001), irrespective of international prognostic index score and cell of origin. In conclusion, the results from this prospectively acquired large cohort corroborated previously published data from smaller sample sizes showing that end-of-treatment PET CR is an independent predictor of PFS and OS and a promising prognostic marker in DLBCL. Long-term survival analysis confirmed the robustness of these data over time. Additional meta-analyses including other prospective studies are necessary to support the substitution of PET CR for PFS as an effective and practical surrogate end point. This trial was registered at www.clinicaltrials.gov as #NCT01287741.
Keywords: Lymphoma, Large B-Cell, Diffuse; Antineoplastic Combined Chemotherapy Protocols; Positron-Emission Tomography; Progression-Free Survival; protokoly protinádorové kombinované chemoterapie; retrospektivní studie; Humans; lidé; difúzní velkobuněčný B-lymfom; pozitronová emisní tomografie; PET/CT; Positron Emission Tomography Computed Tomography; Retrospective Studies; doba přežití bez progrese choroby